Integrated D-InSAR and Ground-based Radar for Open Pit Slope Stability Monitoring and Implications for Rock Mass Young’s Modulus Reduction - Faris Ridwan Maulana; Ridho Kresna Wattimena; Budi Sulistianto (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Excavation and material stockpiling activities in the mining process cause a change in the distribution of forces and stresses in the material. As a result, the material will seek a new equilibrium by releasing the load through a landslide. As part of mitigation, it is necessary to monitor displacements occurring on slopes using high-accuracy devices. Ground-based radar is a technique considered to have good ability to detect displacements in real-time. However, ground-based radar has a weakness in that it cannot detect vertical displacement. One of the emerging technologies that is used for monitoring vertical displacements as LoS displacements is D-InSAR analysis. With the integration of both methods, displacements that occur horizontally and vertically on a slope can be detected properly. In addition, the decrease in rock mass strength due to displacement can be predicted based on numerical analysis using the finite element method. Monitoring was carried out from December 10th, 2021 to April 9th, 2022. The monitoring results from the beginning to the end of the period showed that the horizontal and vertical displacements that occurred in the low wall area were 1247.34 mm and 292.5 mm, respectively. Correlated with these conditions, the Young’s modulus value of the rock mass decreased between 3% and 35%.